(untitled) (Revista "Boletín el Conuco", 2021)
The objective of the article consisted of reviewing the existing documentation on the application and implementation of tax planning, in order to establish whether it is feasible to conceive it as an improvement strategy in the management of tax processes to counteract problems of this type in the small and medium businesses. The method responds to a qualitative analysis of secondary information, built from bibliographic searches of articles and papers published in scientific databases. Multiple results were found that speak of the importance, the process for its applicability and benefits generated by tax planning, mostly dedicated to large companies, susceptible to transfer and adapt to smaller ones, given the scarcity of literature focused on this type of entities. In the discussion the possibilities and effects of tax planning in small and medium-sized companies are analyzed. As one of the main conclusions, tax planning is viewed as a strategy that generates benefits for the companies under analysis